2020
DOI: 10.1016/j.cub.2020.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Enduring Behavioral Effects Induced by Birth by Caesarean Section in the Mouse

Abstract: Highlights d C-section leads to changes in Bifidobacterium spp. abundance in early life d Mice born by C-section have behavioral deficits throughout their lifespan d Co-housing C-section-born mice with vaginally born mice corrects social deficits d B. breve or a dietary prebiotic mixture improves behavior in C-section mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 78 publications
1
61
2
1
Order By: Relevance
“…Preclinical models highlight how gut microbiota disturbances due to antibiotics, delivery mode, or fecal microbiota transplantation (FMT) from AN patients correlated with anxiety-like behaviors [ 38 , 39 , 40 , 41 ]. Lach et al, assessed the long-term effects of transient gut microbiota depletion using a cocktail of five antibiotics in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical models highlight how gut microbiota disturbances due to antibiotics, delivery mode, or fecal microbiota transplantation (FMT) from AN patients correlated with anxiety-like behaviors [ 38 , 39 , 40 , 41 ]. Lach et al, assessed the long-term effects of transient gut microbiota depletion using a cocktail of five antibiotics in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, another recent study in mice found transient hippocampal changes, as well as differences in vocalisation patterns and grooming behaviours, although it was concluded that there were no long‐term consequences of CS delivery based on a lack of differences in neuronal activity in the hippocampus, as well as anxiety‐related and social behaviour tests 207 . Finally, and most recently, a study of mice delivered by CS found social and cognitive deficits along with an anxious phenotype, which were all partially normalised by housing with VD mice 208 . Most likely, the enduring consequences of CS delivery arise from disruptions to both tocosematic processes and dysbiosis.…”
Section: Known Associations Of Caesarean Delivery With Developmental mentioning
confidence: 99%
“…207 Finally, and most recently, a study of mice delivered by CS found social and cognitive deficits along with an anxious phenotype, which were all partially normalised by housing with VD mice. 208 179 and animals. 31…”
Section: The Brainmentioning
confidence: 99%
“…Preclinical animal models have shown that pioneer communities, such as those from the maternal cervicovaginal and gut microbiota, colonize the mucosal surfaces of the newborn and initiate processes that include immune system maturation, nutritional provisioning for the developing brain, and other adaptations to the postnatal environment (Arrieta et al, 2015; Fulde et al, 2018; Gensollen et al, 2016; Jašarević and Bale, 2019; McDonald and McCoy, 2019; Renz et al, 2018; Walker, 2017). Indeed, these animal studies have shown that disruption in this intestinal colonization process promotes lasting changes to the offspring’s immune system, hypothalamic-pituitary-adrenal stress axis, as well as increased susceptibility to allergy, obesity, and diabetes across the lifespan (Al Nabhani et al, 2019a, 2019b; Arrieta et al, 2015; Jašarević et al, 2015, 2017, 2018; Morais et al, 2020; Sudo et al, 2004). While such studies support the notion that vertical transmission of maternal microbiota impacts offspring development in a composition-dependent manner, the specific health outcomes following colonization by a nonoptimal CST IV cervicovaginal microbiome, especially in the context of a high-risk pregnancy, have not been examined.…”
Section: Introductionmentioning
confidence: 99%